Topographic association between active gastritis and Campylobacter pylori colonisation. Issue 8 (August 1989) - Bayerdörffer, E; Oertel, H; Lehn, N; Kasper, G; Mannes, G A; Sauerbruch, T; Stolte, M
Abstract : One thousand biopsy specimens obtained from 10 sites in the stomachs of 50 patients were examined for the presence of active chronic gastritis and Campylobacter pylori. All 32 patients with active chronic gastritis at 234 out of 320 sites were positive for C pylori: 227 showed colonisation with C pylori by the Warthin-Starry stain; and 222 were positive by culture. C pylori was not found in 18 patients with inactive chronic gastritis or histologically normal mucosa. The area of C pylori colonisation was larger than the area of active chronic gastritis in 289 positive specimens on culture and 261 on staining, respectively, suggesting that C pylori colonisation may precede the development of active chronic gastritis. It is concluded that patchy distribution of active chronic gastritis and C pylori colonisation must be considered, particularly in serology or breath test studies where the histological examination serves as a reference. Furthermore, it may have important implications for the follow up of patients after antibacterial treatment. The topographic and specific association of C pylori and active chronic gastritis provides further evidence for the pathogenic role of C pylori in active chronic gastritis.